An Overview of Effective Herbal and Antioxidant Compounds on Diabetes - Khazaei, Mohammad Rasool; Makalani, Fatemeh; Ghanbari, Elham; Fayzemahdavi, Maryam; Khazaei, Mozafar (Journal of Contemporary Medical Sciences, 2018)
Objective: The aim of present study was to review the effect of herbal medicine and antioxidant compounds on diabetes. Methods: We searched PubMed, Science Direct, Scopus, and Medline for studies published from 2000 to 2017 with using keywords of diabetes, herbal medicine, and antioxidant compounds. Results: Various herbal medicines have been introduced to cure the diabetes. The most common types of effective compounds include flavonoids, terpenoid, carotenoids and alkaloids which are able to reduce the levels of blood sugar via increase insulin levels or reduction of intestinal uptake of glucose and regenerate pancreatic tissue through different mechanisms. Conclusion: Herbal medicines with antidiabetic effects can give raise a field to discover drugs with herbal origin for treating the diabetes. Different herbal remedies have been known and proved that mechanism of action.